New diarylamides and diarylureas possessing 8-amino(acetamido) quinoline scaffold: Synthesis, antiproliferative activities against melanoma cell lines, kinase inhibition, and in silico studies - Koh, Eun Jeong; El-Gamal, Mohammed I.; Oh, Chang-Hyun; Lee, So Ha; Sim, Taebo; Kim, Garam; Choi, Hong Seok; Hong, Jun Hee; Lee, Sang-gi; Yoo, Kyung Ho (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2013)
Synthesis of a new series of diarylureas and diarylamides possessing 4-aryl-8-amino(acetamido)quinoline scaffold is described. Their in vitro antiproliferative activities against ten melanoma cell lines were tested. Compounds 11, 21, 3c, and 4c showed the highest potency against A375P cell line with IC50 values in sub-micromolar scale. Compound 4c was equipotent to Vemurafenib against A375P. In addition, compounds 11, 2a, and 21 showed high potency over the NCI-9 tested melanoma cell line panel. The IC50 values of compounds 11 and 21 were in 2-digit nanomolar scale over four and five cell lines, respectively. Compound 21 showed high, dose-dependent inhibition of ERK kinase. ADME profiling showed that compounds 11, 21, 3c, 4c, and 5b are estimated to be orally bioavailable. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: DERIVATIVES; DESIGN; DISCOVERY; DIAGNOSIS; THERAPY; BRAF